Serological Detection and Differentiation of Entamoeba Histolytica from Non-Pathogenic Species of Entamoeba Parasite (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Background: Entamoeba histolytica is one of the important protozoan parasite which infect human and cause amebiasis, this parasite is worldwide distributed parasite. Materials and Methods: This study carried out in parasitology Lab. In Science college of University of Duhok and all stool samples were collected from Duhok (42 Samples) and Erbil (35 Samples) hospital laboratory. All stool samples (77 Samples) were examined in laboratory by microscopic and serologic (ELISA) examination.Results: By microscopic examination detected 11 positive persons which infection rate of Entamoeba spp.in Duhok city were 26.1% and in Erbil city detected 8 infected persons by Entamoeba spp.,with 22.8% infection rate, but in serological test detected 2 positive persons with infection rate of 4.7% in Duhok city and 2 positive persons with infection rate of 5.7% in Erbil city with Entamoeba histolytica parasite. The current study showed that the microscopic examination for detection of E. histolytica wasn’t exact and true method for diagnosis and the serological test (ELISA) is high sensitive to detection and differentiation between pathogenic and non-pathogenic Entamoeba parasite.